2018
DOI: 10.3389/fped.2018.00022
|View full text |Cite
|
Sign up to set email alerts
|

Association of Picky Eating with Growth, Nutritional Status, Development, Physical Activity, and Health in Preschool Children

Abstract: BackgroundThis study aimed to assess the prevalence of picky eating among preschool children and to evaluate the association between eating behavior and growth, physical activity, development, and health status.MethodsA structured questionnaire was used to conduct a cross-sectional descriptive study of 300 primary caregivers of children aged 2–4 years in Taiwan. Data collected included: demographics, food preferences, eating behavior, body weight, and height, development, physical activity, and records of medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 35 publications
1
50
1
10
Order By: Relevance
“…Previous studies have shown that preschool children's eating behavior is related to kindergarten teachers' education, kindergarten environment [25], peers [26], parents' cognition and behavior [13][14][15] and children's physical activity [27]. Parents play an irreplaceable role in forming their children's dietary behavior [12][13][14][15]; therefore, we focused on the correlation between parental awareness and children's eating behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that preschool children's eating behavior is related to kindergarten teachers' education, kindergarten environment [25], peers [26], parents' cognition and behavior [13][14][15] and children's physical activity [27]. Parents play an irreplaceable role in forming their children's dietary behavior [12][13][14][15]; therefore, we focused on the correlation between parental awareness and children's eating behavior.…”
Section: Discussionmentioning
confidence: 99%
“…In a Korean paediatric gastroenterology clinic, constipation was mentioned as a characteristic of being a picky eater by about 27% of caregivers compared with 13% in a control group. Constipation was more common in picky eaters than non-picky eaters in Taiwan (prevalence of 19% vs 10%) (64) . In Generation R, Tharner et al (13) showed a bidirectional relationship between picky eating and constipation with a 'vicious circle' being set up between them.…”
Section: Health and Developmentmentioning
confidence: 97%
“…Of the 15 studies reviewed, 9 articles were found which mentioned a positive relationship between eating and growth and the 6 articles mentioned were not related. From 9 articles that positively related to the growth of children, 3 articles mentioned the correlation in increasing body weight and 6 articles mentioned the correlation between the occurrence of weight loss (Chao, 2018;Galloway, Watson, Pitama, Farrow, & Llewellyn, 2018;Kwon, Shim, Kang, & Paik, 2017;Viljakainen, Figueiredo, Rounge, & Weiderpass, 2019;Volger et al, 2017). 6 articles that are negatively related, mention that the growth of children remains stable or normal but only related to diet or nutritional intake is even just an excessive concern by parents.…”
Section: Correlate Picky Eating In Children Growthmentioning
confidence: 99%